Pediatric multicenter cohort comparison of percutaneous endoscopic and non-endoscopic gastrostomy technique outcomes. (February 2020) - Kumar, Ashwath S; Bani Yaghoub, Majid; Rekab, Kamel; Hall, Matt; Attard, Thomas Mario
Enteral access is one of the mainstays of nutritional support. Several different modalities for gastrostomy placement are established. In pediatrics, however, there is a limited evidence base supporting the choice of 1 modality over the others. We retrospectively compared elective percutaneous endoscopically placed gastrostomy (PEG) with surgical and interventional radiology-placed gastrostomy outcomes using the Pediatric Hospital Inpatient Sample multicenter administrative database (Pediatric Health Information System). Pediatric patients (<18 years) undergoing planned elective gastrostomy (2010–2015) were included. Coded gastrostomy procedure subtype, patient demographic characteristics, chronic comorbidities and subsequent related outcomes, mortality, readmission, length of stay and total cost of admission were analyzed. Univariate analysis differentiated among gastrostomy techniques. The effect of gastrostomy on mortality and 30-day readmission were determined using a forward, stepwise, binary logistic regression. Generalized linear models were used to estimate the effect of gastrostomy type on length of stay and total cost. During the study period, 11, 712 children underwent gastrostomy, including PEG (27%). Patients with chronic comorbidities were more, or as likely to undergo non-PEG procedures. Postoperatively, PEG patients were less likely to require mechanical ventilation and total parenteral nutrition (TPN). Gastrostomy type was not predictive of mortality; predictors included non-White race and need for mechanically assisted ventilation. Readmission following gastrostomy was common (29.5%), and more likely in PEG patients (OR 1.31). Predictors of readmission included earlier TPN (OR 1.39), cardiovascular (OR 1.17) and oncology (OR 4.17) comorbidities. Our study suggests that PEG placement entails similar length of stay and cost as in non-PEG gastrostomy. Patients undergoing PEG were less likely to require mechanical ventilation and TPN postoperatively. Mortality is similar in both groups although more likely with specific comorbidities. Racial background appeared to be associated with choice of gastrostomy, length of stay and mortality.